Legal analysis of the protection of the rights of suspects and defendants from a human rights perspective (Study of constitutional court decision number 61/PUU-XX/2022) - Abelia Permatasari (Universitas Negeri Yogyakarta, 2025)
This study examines the legal protection of the rights of suspects and defendants in the Indonesian criminal justice system from a human rights perspective, with a particular focus on Constitutional Court Decision Number 61/PUU-XX/2022. The research adopts a normative juridical method by analyzing constitutional provisions, statutory regulations, international human rights instruments, and judicial precedents. The findings demonstrate that the Constitution and the Criminal Procedure Code (KUHAP) guarantee fundamental rights such as the presumption of innocence, the right to legal counsel, and freedom from arbitrary arrest and detention. However, in practice, these guarantees are often undermined by law enforcement authorities, leading to violations of due process of law. The Constitutional Court decision provides a progressive interpretation by affirming that restrictions on individual rights must be based on law, proportionate, and aimed at protecting broader public interests. It also emphasizes the non-derogable nature of certain rights, particularly access to legal assistance and protection against arbitrary detention. This ruling is significant not only for strengthening the protection of suspects and defendants but also for shaping ongoing reforms of the Criminal Procedure Code in alignment with international human rights standards. The study contributes to academic discourse on criminal justice reform and offers practical implications for legislators, law enforcement officials, and policymakers in ensuring a more just and democratic legal system.